Untargeted tandem mass spectrometry-based molecular network and zebrafish embryotoxicity and teratogenic effects of Christia vespertilionis (L. F.) Bakh. F. leaf extract - Norazhar, Anis Irfan (2020)
Christia vespertilionis (L.f.) Bakh. f., is a non-climbing ornamental plant with unique butterfly-shaped leaves, hence its vernacular name ‘butterfly wing’ or ‘pokok rerama’ in Malay. In Malaysia, the green-leafed variety gained popularity in recent years due to testimonial reports by local users and distributors for its medicinal uses, which included among others, as a cure for cancer. Despite these popular uses, there is very limited information on the chemical constituents of the species, presenting a significant gap in the cheminformatics of the species. Additionally, more information on the safety profile of the plant is required, towards safeguarding consumer safety. Therefore, the primary objectives of the present study were to establish the chemical profile of the green-leafed variety of the plant, specifically the leaf extract and to evaluate the extract for potential toxicity effects. The metabolite profile of the leaf methanolic extract was established by deploying untargeted tandem mass spectrometry-based molecular networking approach. The toxic effects of the extract involving mortality rate, heartbeat rate, hatchability rate, and spontaneous tail coliling as well as the teratogenic effects were determined on zebrafish (Danio rerio) embryos, as the in-vivo assay model. Zebrafish embryos at 5 hour post-fertilization (hpf) were exposed to 50, 100, 200, 400, and 800 μg/mL of the extract up to 120 hpf. The multi-informative molecular map generated for the leaf metabolome permitted the putative identification of 62 metabolites, comprising 10 C-glycosylflavones, 2 mono- and 2 di-hydroxyflavones, 1 flavone-C,O-diglycoside, 3 flavonol-3-O-glycosides, 15 phenolic acids, 1 phenethyl glycoside and 1 its derivative, 4 hydroxyjasmonic acid derivatives, 4 carotenoids, 2 chlorophylls, 3 monoacylglycerols, 1 sphingolipids, 4 amino acids, 1 nucleoside, 3 organic acids, 1 coumarin derivative and 4 fatty acid amides. As a means of structural validation, two unknown chemical constituents were targeted for isolation which subsequently resulted in their characterization as apigenin-6-C-β-D-glucoside 4ʹ-O-α-D-apiofuranoside [2] and apigenin-6-C-β-D-[(4ʹʹ,6ʹʹ-O-dimalonyl)-glucoside] 4ʹ-O-α-D-apiofuranoside [10], which were newly reported in the plant kingdom as the new derivatives of apigenin-6-C-β-D-glucoside. In the toxicity assay, the median lethal concentration (LC50) value of the extract was determined to be 419.84 μg/mL, which was classified as safe. Nevertheless, from evaluation of possible teratogenic effects on zebrafish embryos, it was further revealed that the extract was toxic at higher concentrations starting from 200 μg/mL onwards with multiple signs of developmental defects. The magnitude of these defects was observed to be concentration-dependent. Moreover, no hatching and spontaneous movement of tail coiling were observed at concentrations of 400 and 800 μg/mL due to the delayed growth and early mortality, respectively. A significant reduction in heartbeat rate was also recorded in all surviving embryos at 400 μg/mL. The present study has provided some important insights on the plant’s chemical and biological characteristics which are a pre-requisite to further research towards its valorization as a candidate in phytotherapy. Further extensive studies of the leaf extract using other animal models as well as the in-vitro assay are required for the establishment of its safe dose for human consumption.